Among Multiple Mental Health Symptoms, Only Attention Deficit/Hyperactivity Problems Predict Poorer BMI Outcomes in Family‐Based Behavioural Treatment for Youth With Severe Obesity - Vilde A. Skodvin; Hanna F. Skjåkødegård; Helge Molde; Denise Wilfley; Rachel P. K. Conlon; Pétur B. Júlíusson; Yngvild S. Danielsen (Pediatric Obesity, 2026)
ABSTRACT Large variability exists in outcome following Family‐based treatment (FBT) for severe obesity in youth. In the present study, we aimed to expand our understanding of how mental health impacts FBT outcomes. In total, 90 participants (58.9% girls) 5.9–18.6 years (mean ± SD: 13.2 ± 3.1) were enrolled in a 17‐session FBT‐programme. Baseline mean percentage above the IOTF threshold for overweight (%IOTF25) was 146 ± 13, and Body Mass Index standard deviation score (BMIz) was 3.02 ± 0.52. Mental health predictors were assessed using the Self‐Perception Profile for Children and the Child Behaviour Checklist. A multivariate multilevel Bayesian linear mixed‐effects model with repeated measures was utilized to estimate the effects of mental health predictors on BMI outcomes. Average change in BMI during FBT was −3.80 (%IOTF25) and −0.08 (BMIz) units. Higher scores of Attention Deficit/Hyperactivity (ADH) Problems were associated with a smaller reduction in BMI (0.31 units for %IOTF25 ( p = 0.02), 0.01 units for BMIz ( p = 0.03) for each one‐unit T‐score increase on the ADH problem scale). Self‐Worth, Emotional Dysregulation, Internalizing‐ and Externalizing problems were not associated with differences in BMI outcomes. Identifying children with higher ADH problems and incorporating additional family support strategies within FBT should be a focus for further treatment development.